PENGARUH METODE PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Gestio Prabaswara, Galih; Nindiasari, Hepsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the impact of the flipped classroom learning method on the mathematical problem-solving skills of junior high school students, specifically focusing on the topic of Linear Equations and Inequalities in One Variable. Conducted at SMP Negeri 1 Tigaraksa during the even semester of the 2025/2026 academic year, this research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The population comprised all seventh-grade students, from which a sample of 64 students was drawn using cluster random sampling, divided equally into an experimental class (32 students) and a control class (32 students). Data collection relied on essay tests administered as pretests and posttests to measure problem-solving proficiency. The statistical analysis revealed a significant difference, where the experimental group achieved a much higher average posttest score (82.40) compared to the control group (71.30). The independent sample t-test yielded a significance value of 0.000 < 0.05, leading to the rejection of the null hypothesis. Therefore, it is concluded that the implementation of the flipped classroom method significantly enhances students' mathematical problem-solving capabilities.